Total Antioxidant and Oxidant Status and DPPH Free radical activity of Euphorbia eriophora - Hasan Akgül; Falah Saleh Mohammed; Eylem Kına; İmran Uysal; Mustafa Sevindik; Muhittin Doğan (Turkish Journal of Agriculture: Food Science and Technology)
Plants have been used for many purposes in different communities. Plants used in alternative medicine since ancient times have been the main material in the treatment of many diseases. In this context, it is very important to determine the biological potential of plants. In our study, total antioxidant status, total oxidant status, oxidative stress index and DPPH free radical scavenging activity of Euphorbia eriophora Boiss. were determined. The aerial parts of the plant were extracted with ethanol in a Soxhlet device. TAS, TOS and OSI values of the plant extract were determined using Rel Assay kits. In addition, the free radical scavenging activity of the plant extract was measured by the DPPH method. As a result of the studies, the TAS value of the plant extract was 5.390±0.227, the TOS value was 20.971±0.348, and the OSI value was 0.390±0.014. The DPPH activity of the plant extract was determined to have an inhibition value of 68.721±1.694% at 2 mg/mL concentration. As a result, in our study, it was determined that E. eriophora has antioxidant potential and can be used as a natural antioxidant agent in this context.